The criminalization of the trade in wildlife - Uhm, Daan P. van (Organized crime in the 21st century, 2023)
In the twentieth century, the damage from unregulated trade in wildlife became transparent as many species became extinct or were on the brink of extinction. Consequently, various moral entrepreneurs emerged to underline the need for regulation. The effect of these initiatives to protect endangered species was divergent. On the one hand, protecting species was regularly faced with the economic and personal interests of powerful stakeholders stagnating any conservation initiatives. On the other hand, European imperialists enhanced the exclusion of local people in order to protect nature reserves and their species. In the late 1900s, public concern increased and international agreements were signed at the initiative of Western countries. The criminalization of the trade in wildlife in the twentieth and twenty-first centuries will be discussed in this chapter to understand the social construction of wildlife trade as a serious crime, being controlled by organized crime networks.